Study of ethanol fermentation reaction using Saccharomyces diastaticus in a two-tank fermentation system with cell recycling - Lerkkasemsan, Nuttapol; Lee, Wen Chien (My University, 2018)
Experimental data of ethanol fermentation in a two-tank system with cell recycling using sucrose as a substrate were investigated to establish a kinetic model that described the reaction. Flocculent yeast Saccharomyces diastaticus LORRE-316 was used as the fermenting yeast, and the fermentation medium comprised 80 g/L sucrose, 10 g/L yeast extract, 10 g/L peptone, 2 g/L potassium phosphate monobasic (KH2PO4), and 0.5 g/L magnesium sulfate heptahydrate (MgSO4·7H2O). Three models, the Monod model, the modified Monod model, and the extended-modified Monod model, were used to describe fermentation, and the extended-modified Monod model described the reaction more accurately than the other two models. The model took substrate limitations plus substrate and ethanol inhibitive effects into consideration, and was modified to include assumptions that included terms for substrates (sucrose, glucose and fructose) and product (ethanol). In addition, the ethanol concentration had a significant effect on cell growth. The results of Lineweaver–Burk plots showed that the maximum specific growth rate (μMAX) and the Monod constant (KS) were 0.72/h and 26.77 g/L, respectively. The models were suitable for describing the experimental data.
Keywords: Ethanol production; Fermentation; Growth kinetics; Metabolic analysis; Modeling; Saccharomyces diastaticus